Autrebiography: J.M. Coetzee's Boyhood and Youth. - Lenta, Margaret (English in Africa, 2003)
The first volume of J. M. Coetzee's autobiography, or autobiographical fiction, "Boyhood," appeared in 1997 and its sequel, "Youth," in 2002. A striking feature of both these works is that the author, while naming the protagonist within them John Coetzee, refers to this younger self in the third person. Critics of Coetzee's works, like Peter Porter and Pankaj Mishra, do not have any idea of the complex relationship of intimacy and detachment which Coetzee has achieved with his protagonist, most obviously through his use of the third person.